2015
DOI: 10.4314/ahs.v14i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cases with a preliminary diagnosis of Crimean- Congo hemorrhagic fever and comparison of characteristics in patients admitted to a secondary care hospital in Kastamonu, Turkey.

Abstract: Abstract:Background: Crimean-Congo hemorrhagic fever (CCHF) is an endemic disease in Turkey. The clinical presentation and laboratory findings are not specific especially in cases without hemorrhagic findings. Objective: We aimed to evaluate CCHF cases and compare them with non-CCHF cases in terms of their characteristics during admission. Methods: Cases with a preliminary diagnosis of CCHF at a secondary care hospital in Kastamonu in 2013 were evaluated, retrospectively. Cases testing RNA/IgM positive were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
3
1
1
Order By: Relevance
“…Contact with animals was more commonly reported in CCHF cases than non-CCHF cases, but, a history of tick bite was similar between the two groups in Bolu, Turkey17. Similar to a previous study conducted in our hospital19, we found that the frequency of tick bites was significantly higher in CCHF cases than non-CCHF cases (p<0.05). Other endemic tick-borne diseases in Kastamonu are tularemia and rickettsiosis, however their clinical presentations are greatly different from CCHF.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Contact with animals was more commonly reported in CCHF cases than non-CCHF cases, but, a history of tick bite was similar between the two groups in Bolu, Turkey17. Similar to a previous study conducted in our hospital19, we found that the frequency of tick bites was significantly higher in CCHF cases than non-CCHF cases (p<0.05). Other endemic tick-borne diseases in Kastamonu are tularemia and rickettsiosis, however their clinical presentations are greatly different from CCHF.…”
Section: Discussionsupporting
confidence: 85%
“…In our hospital, 342 CCHF cases were diagnosed between 2005–2010 and the fatality rate was reported to be 2.9%15. However, 19 CCHF cases were diagnosed in our hospital in 2013 and the fatality rate was determined as 5.3%19. In our study, 31 cases were diagnosed with CCHF in 2014–2017 and the fatality rate was 9.6%.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Aynı zamanda bu parametreler, prognozu öngörmede sıklıkla kullanılmaktadır 12 . KKKA olgularda en sık görülen semptomlar ise sırasıyla ateş, baş ağrısı, kas ağrısı, bulantı, kusma, karın ağrısı, ishal ve hemorajik bulgular olarak belirtilmektedir 13 . Ayrıca birçok farklı çalışmada benzer klinik ve laboratuvar bulgularına değinilmiştir 14,15 .…”
Section: Discussionunclassified
“…Turkish workers report on Crimean-Congo haemorrhagic fever and clinical laboratory diagnosis. 16 In a unique article, Simon Ndira and others report on their experience on tackling malaria by medical students and communities in Eastern Uganda, 17 while Eric Some et al report on PMTCT of HIV in Burkina Faso -that land of upright people. 18 Screening for vancomycin-resistant enterococci is possible but not cost effective so conclude Turkish researchers.…”
mentioning
confidence: 99%